Safety Assessment of Tunnel Lining Structure with Underlying Cavities Based on Fuzzy Comprehensive Evaluation in Mudstone Stratum - Yiming Wang; Haoxuan Wang (Journal of Applied Engineering and Technological Science (JAETS), 2024)
This paper presents a study on the structural safety assessment of tunnel linings with underlying cavities based on a fuzzy comprehensive evaluation model in mudstone stratum. The weight and membership degree are determined using an improved method: field data analysis and numerical simulation. Field data analysis revealed that the proportion of cavities in the surrounding rocks of class ? and at the vault was the largest. Cavity length between 1m and 3m and cavity depth between 20cm and 40cm occupied the most significant proportion. Additionally, the impact of defect parameter changes on structural safety was investigated through numerical simulation. It is well known that the lining safety factors are greatly impacted by changes in surrounding rock classifications, cavity locations and depths. In contrast, changes in cavity lengths do not significantly affect the lining safety. The developed fuzzy comprehensive evaluation model consists of factor set, comment set, membership degree and weight set. They are determined according to the previous field data analysis and numerical analysis results. The developed evaluation model is validated by means of the numerical simulation based on the evaluation work of the specific engineering case.